2009
DOI: 10.1021/ef900711d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure on the Crystallization of Crude Oil Waxes. I. Selection of Test Conditions by Microcalorimetry

Abstract: Evaluations of the potential for formation of wax deposits in laboratories generally are performed on stabilized oil samples, that is, at atmospheric pressure and without the presence of light components. Therefore, the effects to two important factors that influence the solubility of waxes, namely light fractions and pressure, are not considered. As a consequence, the results may not reflect what really happens in production lines and equipment. The high-pressure microcalorimetry technique (HPμDSC) is indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The fact that the crystallization temperatures detected with the spectroscopic technique were slightly higher than those obtained through DSC could be attributed, as previously mentioned, to a potentially greater nucleation effect promoted by ice crystals and/or by the ATR crystal itself. Moreover, these samples were pressed over the ATR crystal which could also affect the phase transition temperature, as it can be observed from a typical phase diagram …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the crystallization temperatures detected with the spectroscopic technique were slightly higher than those obtained through DSC could be attributed, as previously mentioned, to a potentially greater nucleation effect promoted by ice crystals and/or by the ATR crystal itself. Moreover, these samples were pressed over the ATR crystal which could also affect the phase transition temperature, as it can be observed from a typical phase diagram …”
Section: Resultsmentioning
confidence: 99%
“…From phase diagrams, it can be observed that for a fixed temperature, the material state changes if pressure is modified, i.e., when increasing the pressure, the paraffins can be in solid state, even though the temperature is higher than their crystallization temperature. Although phase diagrams only describe ideal systems, the effect of pressure on the crystallization temperature of some alkanes in real systems has been already reported by some authors …”
Section: Resultsmentioning
confidence: 99%
“…So, the use of calorimetric or microcalorimetric methods to determine enthalpy, entropy or free energy can be insightful to infer the nature and magnitude of forces associated with the phenomenon(a) under investigation. [28][29][30][31][32] Different volumes of asphaltene-in-toluene solutions, resin-in-n-heptane solutions and also pure solvents were mixed in this experimental work. Although, it is indisputable that the changes in the solubility parameter affect the interaction between solutes from different solvents, our aim here was to force the asphaltenes (from the toluene solution) to come out of solution, by adding a bad solvent (resins containing n-heptane), thus generating large specific surface area of asphaltene particles (colloidal ones) with which resins (in n-heptane solution) could promptly interact.…”
Section: Isothermal Microcalorimetrymentioning
confidence: 99%
“…The evaluation of the crystallization and deposition of waxes from crude oil is carried out in the laboratory by different testing methods, such as measurement of the wax appearance temperature (WAX) and enthalpy of crystallization; determination of the pour point; the cold finger test; and monitoring the viscosity in function of temperature drop …”
Section: Introductionmentioning
confidence: 99%